Synthesis and immunosuppressive activity of new mycophenolic acid derivatives - Barbieri, Karina P. [UNESP]; Ercolin, Lucas Dos R. [UNESP]; Louat, Thierry; Polesi, Marisa C. [UNESP]; Chin, Chung M. [UNESP]; Zeppone, Iracilda C. [UNESP]; Dos Santos, Jean L. [UNESP] (Bentham Science Publishers, 2017)
Background: Immunosuppressive drugs are widely used to prevent and treat allograft rejection and autoimmune diseases. Mycophenolic acid (MPA) and its derivatives are currently one of the most prescribed immunosuppressive drugs; however, metabolic drawbacks and variable interand intrapatient responses limit their use. Objective: In order to find out new safe and effective immunosuppressive compounds, we report here the synthesis and pharmacological evaluation of hybrid MPA derivatives containing the thalidomide/ phthalimide subunits. Results: All compounds 3a-d exhibited an enhanced ability to reduce the levels of pro-inflammatory cytokines compared to the parental drugs MPA and thalidomide. The mixed lymphocyte reaction assay has demonstrated that compound 3d - (E)-(3-(1,3-dioxoisoindolin-2-yl)-2,6-dioxopiperidin-1-yl)methyl-6-(4-hydroxy-6-methoxy-7-methyl-3-oxo-1,3-dihydroisobenzofuran-5-yl)-4-methylhex-4- enoate - has superior activity compared to that of MPA. In addition, compound 3d was less cytotoxic against Jurkat cells than MPA and did not demonstrate in vivo genotoxic effect. Conclusion: All these data have shown that compound 3d is a promising lead compound useful in the immunosuppressive therapy.
Keywords: Immunossupression; Immunossupressive drugs; Mixed lymphocyte reaction assay; Mycophenolic acid; Thalidomide